1998
DOI: 10.1097/00005373-199803000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Childhood Injury

Abstract: A review of childhood injuries at the Wesley Guild Hospital, a component of Obafemi Awolowo University Teaching Hospital Complex, Ile-Ife, Nigeria, showed that 1,471 patients seen in the children's emergency room during a period of 4 years (1992-1995) were there as a result of trauma, representing 9% of all patients seen. The case notes and accident and emergency cards of 1,224 were available for review. Ages ranged from 2 months to 15 years, with a mean of 6.9 years, and 40% of the patients were between 5 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
47
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 35 publications
12
47
0
Order By: Relevance
“…Other published reports had mentioned violent traumas from gunshot and assaults, rather than RTA, as most common cause of trauma encountered [20]. Assaults from secret cult activities among Nigerian students are another form of trauma which previous reports from Nigeria had not documented [1,6,9,21]. This takes the form of machete cuts and/or gunshot injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Other published reports had mentioned violent traumas from gunshot and assaults, rather than RTA, as most common cause of trauma encountered [20]. Assaults from secret cult activities among Nigerian students are another form of trauma which previous reports from Nigeria had not documented [1,6,9,21]. This takes the form of machete cuts and/or gunshot injuries.…”
Section: Discussionmentioning
confidence: 99%
“…1 On the other hand, Adesunkanmi et al in 1998 reported a study from Nigeria (for the period 1992-1995), stating that most deaths in infants were due to infectious disease processes, but with trauma deaths (especially due to road traffic accidents as the external cause/circumstance of death) being the second most common cause of death. 2 This difference between developed and developing countries has however been changing, with the WHO World Report On Child Injury Prevention (2004 data) indicating that also in developing countries, an increasing number of children are now dying from injury and that head injuries are the single most common type of fatal injury sustained by children. 3 Danseco et al reported (from Maryland, USA) that injury rates increase with age and recorded higher nonfatal injuries amongst the 5-9 year old children, yet the rate for fatal injuries was higher amongst children aged from 0-4 years.…”
Section: Introductionmentioning
confidence: 99%
“…5 Tabish et al reported that in India (2003) the most common cause of head injury was due to falls (68.2%), followed by transportation accidents (28%), assault (2%) and injuries due to flying objects (2%). 6 Head injury as a result of falls was stated to be the third leading cause of death in children aged [1][2][3][4] years, according to a study from Chicago (Hall et al, 1989). 7 There appears to be minimal recent published literature on the fatal head injuries in the pediatric population.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27] In our study too, boys were more commonly (63.21%) hospitalized than girls (36.79%), Male children are given more freedom, opportunities, and facilities than females in all aspects in our society. Likewise, they are more exposed to potential risk factors and potential environment suitable for trauma such as playing on roads, rooftop, on trees, or near construction sites.…”
Section: Discussionmentioning
confidence: 91%